Pengaruh Kemampuan Baca Tulis Al-Qur’an terhadap Hasil Belajar Siswa pada Mata Pelajaran Al-Quran Hadis di MTS Mathla’ul Anwar Sukaluyu Kecamatan Nanggung - Mira Andayani; Ery Subaeri Ahmad; Maturidi Maturidi (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2021)
Abstract This research has a purpose namely to know whether the ability to write Al-Qur’an has an effect on learning outcomes in the Qur’anic Hadits class VII MTs Mathlaul Anwar Sukaluyu 2020-2021 year. As for this research method requires several things, the research design using a quantitative approach, the variables in this description are 2, namely the ability to write Al-Qur’an and the results of learning Al-Qur’an Hadits lessons, this research method also requires a research population with a research sample of 43 students of grade VII MTs Mathlaul Anwar Sukaluyu. Then the data source consisting of primary data sources and secondary data sources. In addition, the authors also use data collection methods consisting of documentation methods. Then process the data that has been obtained by using the product moment formula and simple regression so that the results of this study can be seen. The result of this study indicate that the ability to read and write Al-Qur’an at MTs Mathlaul Anwar Sukaluyu Kec. Nanggung Kab. Bogor especially in class VII, is categorized as quite good. This is evidenced by the results of the test of reading and writing ability of the Qur’an as a variable (X) with an average value of 66.4 and and standard deviation of 9.14. while the learning outcomes in the subject of the Qur’an Hadits at MTs Mathlaul Anwar Sukaluyu Kec. Nanggung Kab. Bogor 2020-2021 year in class VII obtained the results of the study of calculating the average value of the variable (Y) namely learning outcomes of 66.5 and a standard deviation of 8.11, this is in the quite good category. To find out the effect of the ability to write Al-Qur’an on the learning outcomes in the Qur’an class VII MTs Mathlaul Anwar Sukaluyu, the writer used the product moment correlation test and regression test. From the calculation of the product moment correlation test, the correlation index is obtained = 0.839. After obtaining the correlation index, then consulted with the 5% and 1% significance levels with the assumption, if (1%) means significant, it means the hypothesis is accepted. Because and (0,389) at a significant level of 5% and 1%, it means that it is significant, meaning that the hypothesis is accepted. If interpreted in the table of the correlation coefficient interpretation scale the level of the relationship between the ability to read and write Al-Qur’an and learning outcomes in the class VII MTs Mathla’ul Anwar Sukaluyu Kec. Nanggung Kab. Bogor 2020/2021 Year, was verry strong. As the calculation of the Determinant Coefficient, variable X (Ability to Read and Write Al-Qur’an) contributes or contributes 70.39% to variable Y (Learning outcomes of the Qur’an Hadits ). From the results obtained from the calculation of the regression test. It is obtained for 97.8, if then reject Ho means significant. Because, it can be concluded that the data are significance, either at the data are significant, either at the 5% or 1% significance level. This means that there is a significant influence between the Ability to Read and Write Al-Qur’an on learning outcomes in the Qur’anic Hadits subject for class VII of MTs Mathla’ul Anwar Sukaluyu, Nanggung District, Bogor Regency, 2020/2021 academic year.